Immature reticulocytes are sensitive and specific to low‐dose erythropoietin treatment at sea level and altitude. Issue 7 (29th March 2021) - Jeppesen, Jan Sommer; Breenfeldt Andersen, Andreas; Bonne, Thomas Christian; Thomassen, Martin; Sørensen, Helle; Nordsborg, Nikolai Baastrup; Olsen, Niels Vidiendal; Huertas, Jesús Rodríguez; Bejder, Jacob
Abstract: We investigated whether immature reticulocyte fraction (IRF) and immature reticulocytes to red blood cells ratio (IR/RBC) are sensitive biomarkers for low‐dose recombinant human erythropoietin (rhEpo) treatment at sea level (SL) and moderate altitude (AL) and whether multi (FACS) or single (Sysmex‐XN) fluorescence flow cytometry is superior for IRF and IR/RBC determination. Thirty‐nine participants completed two interventions, each containing a 4‐week baseline, a 4‐week SL or AL (2, 230 m) exposure, and a 4‐week follow‐up. During exposure, rhEpo (20 IU kg −1 ) or placebo (PLA) was injected at SL (SLrhEpo, n  = 25, SLPLA n  = 9) and AL (ALrhEpo, n  = 12, ALPLA n = 27) every second day for 3 weeks. Venous blood was collected weekly. Sysmex measurements revealed that IRF and IR/RBC were up to ~70% ( P  < 0.01) and ~190% ( P  < 0.001) higher in SLrhEpo than SLPLA during treatment and up to ~45% ( P  < 0.001) and ~55% ( P  < 0.01) lower post‐treatment, respectively. Compared with ALPLA, IRF and IR/RBC were up to ~20% ( P  < 0.05) and ~45% ( P  < 0.001) lower post‐treatment in SLrhEpo, respectively. In ALrhEpo, IRF and IR/RBC were up to ~40% ( P  < 0.05) and ~110% ( P  < 0.001) higher during treatment and up to ~25% ( P  < 0.05) and ~40% ( P  < 0.05) lower post‐treatment, respectively, compared with ALPLA . Calculated thresholds provided ~90% sensitivity for both biomarkers at SL and 33% (IRF) and 66% (IR/RBC) at AL. Specificity was >99%. Single‐fluorescence flow cytometry coefficient of variation was >twofold higher at baseline ( P  < 0.001) and provided larger or similar changes compared to multi‐fluorescence, albeit with smaller precision. In conclusion, IRF and IR/RBC were sensitive and specific biomarkers for low‐dose rhEpo misuse at SL and AL. Abstract : This study investigated whether immature reticulocyte fraction and immature reticulocytes to red blood cells ratio are sensitive biomarkers for low‐dose recombinant human erythropoietin treatment at sea level and moderate altitude.